A longitudinal person-centred approach to the job demands-control model. Issue 6 (1st November 2016) - Mauno, Saija; Mäkikangas, Anne; Kinnunen, Ulla
Abstract : We used a longitudinal design and a person-centred methodology to test the strain and learning hypotheses of the job demands–control model among Finnish employees ( n = 926), who were followed-up at three time points covering a period of 2 years (2008–2010). First, we identified longitudinal subgroups in demands and control across three measurement points. Second, we examined how these subgroups differed in strain (job exhaustion) and motivation-related outcomes (vigour at work, work–family enrichment). Growth mixture modelling revealed four subgroups: "stable high strain", "stable low strain", "increasing control", and "decreasing control". The stable high- and low-strain subgroups also differed in the outcomes studied (exhaustion, work–family enrichment) as suggested by the demands–control model. The findings also suggest that job control is subject to changes over time and that these changes are likely to be associated with changes in employee outcomes. Malleability of job control should be kept in mind in job stress interventions, likewise the fact that some employees suffer from chronic job stress.